Impact of rice minikit trials on the adoption behaviour of farmers - Ramachandran C (Department of Agricultural Extension, College of Agriculture, 1992)
With a view to study the impact of Rice Minikit Trials on adoption behavior of farmers the present investigation was undertaken under the title “Impact of Rice Minikt Trials on the Adoption Behaviour of Farmers”. Impact was measured in terms of the adoption of the selected recommended practices by the participant farmers and the non-participant farmers. The farmer’s perception about the innovation-characteristics of Minikit Variables of Rice, the procedures followed in conducting Rice Minikit Trials, and the constraints faced by the participant farmers and the extension personnel were also analysed.